Isolation, Carriers Selection and Inoculum Formulation of Thiobacillus spp. - Fahrizal Hazra; Enny Widyati (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2007)
One of problems in international trading of coal is high content of suljur. B iodesuljuration of coal using Thiobacillusspp is recognized as the most environmentally friendly to reduce the content. This research was aimed to collect and to isolateThiobacillus spp from coal, acid mine drainage, ex-coal mining soil and agriculture soil, on selected media. Colonies growingon the media were re-isolated for further characterization to find the most similar to Thiobacillus spp. In this experiment, the selected isolate (5, J 0, 20, 50, and J 00 ml) was cultured in 100 g of coal dust, rice husk charcoal, wood charcoal, andactivated charcoal, to find an appropriate inoculum for coal desulJuration. To observe their survival rate, they were reisolated onto 10 ml Thiobacillus broth medium. The re-isolations were observed at the 7, 14, 21 and 28 days of incubation. The results showed that ThiobaciIlus spp was found only in acid mine drainage. After characterization, the isolates were strongly similar to Thiobacillusferrooxidans. The most proper inoculum was 100 ml culture ofThiobacillus in 100 g rice husk charcoal. It had 100% survival rate after 20 days cultured in that carrier.